2022
DOI: 10.3390/jcm11041074
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Multimodal Telemedical Intervention for Patients with Parkinson’s Disease—A Pilot Study

Abstract: Symptoms of Parkinson’s disease (PD) can be controlled well, but treatment often requires expert judgment. Telemedicine and sensor-based assessments can allow physicians to better observe the evolvement of symptoms over time, in particular with motor fluctuations. In addition, they potentially allow less frequent visits to the expert’s office and facilitate care in rural areas. A variety of systems with different strengths and shortcomings has been investigated in recent years. We designed a multimodal telehea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…However, previous research assessing the feasibility of a DHTS in PwP found a completion rate between 62 and 68% over 6 and 13 weeks, respectively, in people mostly scoring II on the Hoehn & Yahr scale ( 43 ). Therefore, as previously done by others over longer time periods (12 weeks) in people with a median Hoehn & Yahr score of II, a completion rate of 68% was used as feasibility threshold in the present study ( 44 ). Here, this threshold was exceeded for all devices which was expected as the monitoring period was much shorter.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research assessing the feasibility of a DHTS in PwP found a completion rate between 62 and 68% over 6 and 13 weeks, respectively, in people mostly scoring II on the Hoehn & Yahr scale ( 43 ). Therefore, as previously done by others over longer time periods (12 weeks) in people with a median Hoehn & Yahr score of II, a completion rate of 68% was used as feasibility threshold in the present study ( 44 ). Here, this threshold was exceeded for all devices which was expected as the monitoring period was much shorter.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID‐19 pandemic, in fact, the possibility of supporting patients with telerehabilitation protocols via mobile health, independent of their geographical location, could represent a positive opportunity, considering its accessibility and high motivational power based on the integration of playfulness and gamification 20–22 . Finally, mobile health is flexible, as its use is independent of time and place, and thus adaptable to the daily life of patients 23,24 . It should be considered that previous studies have reported that patients who consider therapy to be useful and motivating show greater therapeutic adherence and involvement in therapy, especially in distant rehabilitation 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 Finally, mobile health is flexible, as its use is independent of time and place, and thus adaptable to the daily life of patients. 23 , 24 It should be considered that previous studies have reported that patients who consider therapy to be useful and motivating show greater therapeutic adherence and involvement in therapy, especially in distant rehabilitation. 25 , 26 Moreover, it has been demonstrated that the use of mobile health can improve functional outcomes, promoting the quality of life of patients, especially in PD.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed 3 eHealth solutions that use different paradigms: (1) guided measurements at specific time points by a camera system; (2) continuous, implicit monitoring of mobility by wearable sensors; and (3) a combination of guided and continuous measurements by a tablet app. The systems were described in detail previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%